2016
DOI: 10.1111/1440-1681.12648
|View full text |Cite
|
Sign up to set email alerts
|

Role of mechanistic target of rapamycin (mTOR) in renal function and ischaemia–reperfusion induced kidney injury

Abstract: Despite the presence of many studies on the role of mechanistic target of rapamycin (mTOR) in cardiorenal tissues, the definitive role of mTOR in the pathogenesis of renal injury subsequent to ischaemia-reperfusion (IR) remains unclear. The aims of the current study were to characterize the role of mTOR in normal kidney function and to investigate the role of mTOR activation in IR-induced kidney injury. In euvolemic anaesthetized rats, treatment with the mTOR inhibitor rapamycin increased blood pressure (121 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This was observed in the absence of any rapamycin effects on the acute autoregulation of renal blood flow. Previous studies have found that acute administration of rapamycin had no significant effect on urine volume or sodium excretion as studied in mice, 37 rats, 9,38 and pig. 39 This would suggest that in the presence of rapamycin the elevated RPP may have either enhanced the expression or activity of tubular sodium transporters or suppressed the production of natriuretic substances.…”
Section: Mtorc1-rapamycin Effects On Pressure-natriuresismentioning
confidence: 85%
“…This was observed in the absence of any rapamycin effects on the acute autoregulation of renal blood flow. Previous studies have found that acute administration of rapamycin had no significant effect on urine volume or sodium excretion as studied in mice, 37 rats, 9,38 and pig. 39 This would suggest that in the presence of rapamycin the elevated RPP may have either enhanced the expression or activity of tubular sodium transporters or suppressed the production of natriuretic substances.…”
Section: Mtorc1-rapamycin Effects On Pressure-natriuresismentioning
confidence: 85%
“…18 Wang et al have confirmed that the mTOR pathway plays distinct roles in the process of inflammation and acute lung injury (ALI). 20 Moreover, the mTOR pathway was also reported to exert effects on ALI in mice by mediating mitochondrial autophagy of lung tissue cells. 20 Moreover, the mTOR pathway was also reported to exert effects on ALI in mice by mediating mitochondrial autophagy of lung tissue cells.…”
Section: Introductionmentioning
confidence: 99%
“…19 The mTOR pathway affects I/R injury in kidneys by regulation of mitochondrial autophagy. 20 Moreover, the mTOR pathway was also reported to exert effects on ALI in mice by mediating mitochondrial autophagy of lung tissue cells. 21 Therefore, the current study was performed aiming to elucidate the mechanism by which mitochondrial autophagy exerts its effect on lung I/R injury by regulating the mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms regulating autophagy in AKI are not clearly understood and are thought to be negatively regulated in part by mammalian/mechanistic target of rapamycin (mTOR). However, mTOR has competing effects on cell growth, metabolism, and survival, and pharmacological agents that inhibit mTOR (and thus promote autophagy) do not routinely protect the renal parenchyma from IRI (11, 12). Further work is required to identify molecular regulators of autophagy as well as pharmacological agents that selectively, and beneficially, target this pathway.…”
mentioning
confidence: 99%